2020
DOI: 10.1155/2020/7201379
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori Infection and Diabetes: A Cross-Sectional Study in China

Abstract: Background. Studies suggest an association between H. pylori infection and extragastrointestinal disease. Limited studies provided conflicting results on the association between H. pylori infection and diabetes. The present study was aimed at examining the association between H. pylori infection and diabetes in a large health checkup population in China. Methods. A cross-sectional study was conducted; participants who attended health checkups at Beijing MJ Health Screening Center during 2017-2018 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
(54 reference statements)
1
9
0
2
Order By: Relevance
“…De este modo, Zhang y col. (17), reportan tasas de infección superiores al 50 % en pacientes menores de 40 años comparado con los mayores de 50 años (P < 0,001); y Smith y col., informan de un 43 % en pacientes de 31 a 40 años (15). Sin embargo, en otros estudios se demuestra más probabilidad de infección en adultos mayores (12) o simplemente no se encontraron diferencias entre los grupos etarios (13,16).…”
Section: Discussionunclassified
“…De este modo, Zhang y col. (17), reportan tasas de infección superiores al 50 % en pacientes menores de 40 años comparado con los mayores de 50 años (P < 0,001); y Smith y col., informan de un 43 % en pacientes de 31 a 40 años (15). Sin embargo, en otros estudios se demuestra más probabilidad de infección en adultos mayores (12) o simplemente no se encontraron diferencias entre los grupos etarios (13,16).…”
Section: Discussionunclassified
“…By acting on the hormone somatostatin, cag + strains reduce insulin secretion by the pancreas. In addition, H. pylori increase the levels of leptin and ghrelin and predispose people to obesity and diabetes [ 76 , 82 ]. H. pylori cause type II diabetes by disrupting the production and release of plasma lipoproteins and disrupting glucose tolerance and Hb1Ac levels.…”
Section: Discussionmentioning
confidence: 99%
“…According to an analysis of geographical subpopulation regions, the infection risk of H. pylori in the Asian population was slightly higher than that in other populations (Mansori et al, 2020). In contrast, a cross-sectional study showed that there was no significant correlation between H. pylori and diabetes, though it has been estimated that H. pylori may be associated with an increased risk of diabetes in Chinese females (Man et al, 2020). Moreover, an ongoing clinical study may help reveal the association between diabetes and H. pylori infection by investigating the genome-wide association of H. pylori infection (PLCO-989).…”
Section: Endocrine and Metabolic Diseasementioning
confidence: 95%